Customer satisfaction with service delivery in the life insurance industry:an empirical study - Norazah Mohd Suki, (Penerbit Universiti Kebangsaan Malaysia, 2013)
Consumers purchase life insurance for financial security during times of hardship. The present research examines the effects of service quality on customer satisfaction with service delivery in the life insurance industry. A quantitative research method is used to achieve the research objective. One hundred completed and usable self-administered surveys were received from respondents located in the Federal Territory of Labuan, Malaysia that have had a life insurance policy with an insurance company in Malaysia. The empirical results of the multiple regression analysis divulge that assurance, tangibility and empathy have a positive and significant relationship with customer satisfaction with service delivery in the life insurance industry. Customers are satisfied with the way the services are delivered. High levels of skill and experience among employees of a life insurance company and the dedication of agents provide customer confidence. Customer satisfaction is strengthened when agents possess outstanding communication skills and the customer is served in a pleasant atmosphere endowed with appealing physical facilities. As a result, customers are given individualized attention because the staffs understand the specific needs of their customers. Suggestions for future research are also proposed.